Dinâmica populacional do camarão Sicyonia dorsalis (Crustacea: Penaeoidea) no litoral de Cananéia, sul do estado de São Paulo - Silvestre, Ana Karolyne de Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The abundance and spatial structure of a population are strongly influenced by environmental conditions of a region. The aim of this study is to assess the abundance and the spatiotemporal distribution of the shrimp Sicyonia dorsalis in relation of the variation of different environmental factors such as temperature, salinity, grain size and the organic matter in the sediment. Samples were collected monthly during the period of Jul-12 to May-14 in the Cananéia coastal, southern state of São Paulo. Sampling stations were predetermined in estuarine and oceanic zones. Monthly trawls were conducted within duration of 30 minutes in the seven sampling stations using a shrimp boat equipped with double-rig nets. Surface and bottom temperatures and salinities were measured with thermometer and specific optical refractometer, while for sediment sampling was used a Petersen tagger. From January 2013, we performed the monitoring parameters of the water column (surface to the bottom) through a multi-parameter probe (EUREKA). A total of 1154 individuals was collected in the survey area with higher abundance during the spring and winter seasons. On the other hand, few individuals was captured during the summer and autumn. Spatially we observed a higher number of individuals in the oceanic zone (1049). There were significant differences in the abundance of individuals in space and seasons (Kruskal-Wallis, p <0.001). The temperature and salinity were environmental variables that influence the distribution of the abundance of individuals, according to the Linear Multiple Regression (p <0.05). In addition to limiting the environmental factors, the space-time distribution may be related to the kind of life cycle exclusively marine

A abundância e estrutura espacial de uma população são fortemente influenciadas pelas condições ambientais de uma região. O objetivo desse estudo é avaliar a abundância e a distribuição espaço-temporal do camarão Sicyonia dorsalis em relação à variação de diferentes fatores ambientais, como a temperatura, a salinidade, a granulometria e a quantidade de matéria orgânica do sedimento. As coletas foram realizadas mensalmente durante o período de jul/12 a maio/14 no litoral de Cananéia, região sul do estado de São Paulo. As estações de amostragem foram predeterminadas em zonas estuarinas e oceânicas. Arrastos com duração de 30 minutos foram promovidos nas sete estações amostrais utilizando-se um barco camaroneiro equipado com redes double-rig. As temperaturas de superfície e de fundo foram mensuradas com termômetro e a salinidade através de um refratômetro óptico específico, enquanto que para a amostragem do sedimento foi utilizado um pegador de Petersen. A partir de janeiro de 2013, foi realizado o monitoramento de parâmetros da coluna d'água (superfície ao fundo) através de uma sonda multiparâmetro (EUREKA). Um total de 1154 indivíduos foi coletado na região amostrada, com maior abundância durante a primavera e o inverno dos dois anos, sofrendo um decréscimo em sua captura nos meses de verão e outono. Espacialmente, foi observado um maior número de indivíduos na zona oceânica (1049). Houve diferença significativa na abundância de indivíduos espaço-temporalmente (Kruskal-Wallis, p < 0,001). A temperatura e salinidade foram variáveis ambientais que influenciaram na distribuição da abundância dos indivíduos, quando analisadas por meio de Regressão Linear Múltipla (p<0,05). Além da limitação pelos fatores ambientais, a distribuição espaço-temporal pode estar relacionada ao ciclo de vida da espécie exclusivamente marinha
Keywords: Camarão - Distribuição geográfica; Dinâmica populacional; Decapode (Crustaceo); Distribuição espacial da população; Decapoda (Crustacea) - Geographical distribution; Cananeia (SP)